2020
DOI: 10.1016/j.ajogmf.2020.100242
|View full text |Cite
|
Sign up to set email alerts
|

Routine third-trimester ultrasound in low-risk pregnancies and perinatal death: a systematic review and meta-analysis

Abstract: This study aimed to determine whether routine third-trimester ultrasounds in low-risk pregnancies decrease the rate of perinatal death compared with regular antenatal care with serial fundal height measurements. DATA SOURCES: This was a systematic review and meta-analysis of randomized control trials to identify relevant studies published from inception to October 2019. The databases used were Ovid, PubMed, Scopus, ClinicalTrials.gov, and the Cochrane Central Register of Controlled Trials using a combination o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
(18 reference statements)
0
8
0
Order By: Relevance
“…They found that the rate of identification of LGA was higher in the routine ultrasound group (30%) compared with that in the serial SFH measurement group (11%), although there was no significant difference in the incidence of LGA at birth (9% in both groups). The same meta‐analysis did not find a significant difference in perinatal mortality rate between the two groups (ultrasound group, 0.4% vs SFH group, 0.3% (relative risk (RR), 1.14; 95% CI, 0.68–1.89)) 56 . Nor were there any significant differences between the two groups in terms of the rates of stillbirth or neonatal death.…”
Section: Third‐trimester Ultrasound Scanmentioning
confidence: 91%
See 1 more Smart Citation
“…They found that the rate of identification of LGA was higher in the routine ultrasound group (30%) compared with that in the serial SFH measurement group (11%), although there was no significant difference in the incidence of LGA at birth (9% in both groups). The same meta‐analysis did not find a significant difference in perinatal mortality rate between the two groups (ultrasound group, 0.4% vs SFH group, 0.3% (relative risk (RR), 1.14; 95% CI, 0.68–1.89)) 56 . Nor were there any significant differences between the two groups in terms of the rates of stillbirth or neonatal death.…”
Section: Third‐trimester Ultrasound Scanmentioning
confidence: 91%
“…Al-Hafez et al 56 , in a systematic review including seven RCTs and 23 643 women, compared detection of LGA (EFW > 90 th centile) by routine ultrasound examination with that by serial measurements of the symphysis-fundus height (SFH). They found that the rate of identification of LGA was higher in the routine ultrasound group (30%) compared with that in the serial SFH measurement group (11%), although there was no significant difference in the incidence of LGA at birth (9% in both groups).…”
Section: Large-for-gestational Age/macrosomiamentioning
confidence: 99%
“…We are not advocating a routine third trimester ultrasound for every obstetrical patient. Recent trials have shown that routine third-trimester ultrasound in low-risk patients can increase the detection of small-for-gestational age fetuses, 7,8 but these trials and several meta-analyses [7][8][9][10][11] have concluded that a routine third trimester exam in low-risk patients does not reduce perinatal death or improve other perinatal outcomes. Indeed, ultrasound diagnosis of large-for-gestational-age may unnecessarily increase the rate of cesarean birth.…”
Section: Pros and Cons Of Repeat Screeningmentioning
confidence: 99%
“…6 Given the limited predictive value of these risk factors and the potential for human error 2 and concerns regarding equity, 'universal' ultrasound has been explored. 7,8 Evidence suggests this increases the detection rate of birthweight (<10th centile) 7,8 but does not improve perinatal outcomes, 8,9 not least because many SGA babies are not growth-restricted 10,11 and birthweight (<10th centile) constitute less than a quarter of stillbirths. 3 Nevertheless, impaired placental function may be present in about half of stillbirths, 12 and the concept of fetal growth restriction (FGR) has developed.…”
Section: Introductionmentioning
confidence: 99%